INNOVATIONS IN THE EDUCATIONAL PROCESS IN TECHNICAL UNIVERSITIES BASED ON AN ONTOLOGY FOR INTERACTIVE TEACHING SYSTEM (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2021)
This paper aims to highlight the influence of e-Learning platforms and to offer a new perspective based on students' decisions and influenced by their preferences. This is an innovative e-learning module, using a specific methodology that allows students to vote in real-time, during the course, based on electronic votes. The students can choose the level of details they want for each section of the presentation and which example cases are relevant or not for them. This way, a high level of student involvement is maintained during the course, and the information is provided interactively to the participants. The electronic votes of the students are managed using a Moodle platform plugin based on an educational ontology, especially created. These votes will influence the course of the teacher's oral presentation.
Keywords: Educational process; Voting system; Ontology